Innovation and patents as a business success factor - Garavito Hernández, Youseline (2021)
Purpose. The purpose of this paper is to expose the impact of innovation and patent registration, as a strategy that contributes to business success in the current competitive and globalized market conditions. Design/methodology/approach. This paper presents a study on the innovation and contribution of the patent registry in the growth of economic sales of 1,746 companies in the Colombian manufacturing sector, whose applied methodology was a statistical correlation analysis and a binary logistic regression. Findings. The results reveal a positive relationship among incremental product innovations with the achievement of sales success, although it is evident that patent registration negatively influences business success as a factor in innovation. Originality/value. This study allows organizations to understand the importance of developing innovation processes and patent registration as a competitive factor that drives sales growth and success. Doi: https://doi.org/10.1108/JEFAS-09-2019-0218